Preclinical studies of NOS inhibitor T1059 vasopressor activity on the models of acute hemorrhagic shock in rats and dogs - Filimonova, Marina; Shevchenko, Ljudmila; Makarchuk, Victoria; Saburova, Alina; Shegay, Petr; Kaprin, Andrey; Ivanov, Sergey; Filimonov, Alexander (Frontiers in Pharmacology, 2022)
The development of new effective and safe vasopressors is one of the ways to increase the effectiveness of the treatment of hypotensive disorders, the severe forms of which remain a common cause of death in all countries of the world. Previously, we synthesized the original compound T1059, a selective inhibitor of eNOS/iNOS which has a pronounced vasoconstrictive effect. Here we show its vasopressor activity in models of the early stage of acute hemorrhagic shock in rats and dogs, as part of preclinical studies. The results indicate NOS inhibitor T1059 as a potent long-acting vasopressor. Its single parenteral administration in sufficiently safe doses (1/50-1/9 LD10), caused in rats and dogs a rapid increase in vascular tone, accompanied by a prolonged hypertensive effect (within 90-120 minutes in rats, and within 115 min in dogs). The repeated administration of T1059 at low doses (1/3 of the first dose) made it possible to considerably (by at least 60 minutes) prolong a significant vasopressor effect. In all schemes, T1059 administration considerably inhibited the development of threatening cardiorespiratory disorders and significantly (p = 0.0026–0.0098) increased the short-term survival of experimental animals, formally extending the duration of the “golden hour” by 2 times. These data indicate that NOS inhibitors and, in particular, compound T1059, are able to create new opportunities in the treatment of hypotensive disorders, including the provision of assistance at the prehospital stage of treatment of such pathologies.